تأثير التسميد بخليط من مسحوق قشور الموز و البيض علي نمو بادرات وإنتاجية نبات الفلفل الحار Capsicum frutescens L. - محمد معيتيق, فاطمة; ميلاد سويسي, ريما; أحمد فريعة, هاجر (المجلة العلمية لكلية التربية, 2023)
This research discusses the impact of fertilization using a mixture of the eggs shells and banana skin and the production of Capsicum Frutescens with different concentrations (1,3,5,7) g / 300 g. This study discusses the average of measurements of growth, estimation the average of leaf area a, estimation of the percentage of the dry matter , estimation of Chlorophyll (A , B) , estimation of sugar average , estimation of proteins , , estimation of some elements of the sky and soil. where results have showed that fertilization using a mixture of the egg shells and banana skin had an effective impact on most of the growth measurements such as the total length average of the plant , the number of leaves , the number of branches , the number of flowers, the number of fruits , weight of fruits , the average of the overall chlorophyl , the average of wet weight , the average of dry weight , the average of the percentage of dry matter , and also the content of some metabolic processes such as the average of sugar and the average of soluble proteins. Whereas the physio-chemical parameters for the irrigation water like water PH 6.99 and electric conductivity 1583. The average of PH for the mixture of the egg shells and the banana skins 1.98 and the average of soil extract PH , while the average moisture content for the mixture of the egg shells and banana skins powder 92.21.The average of the soil extract of some metallic elements such as potassium and sodium and also its content in the chlorides and carbonate has showed that significant differences in some concentrations. The estimation of some basic elements in the sky like sodium (Na) , potassium (K), cadmium(cd) , calcium (ca) , zinc (Zn) ,lead (P b). From the results obtained , it has been showed that the mixture of the egg shells and the banana skins powder has an effective role in the growth and the production of capsicum frutescens especially